Adaptation pathways identify effective strategies for mitigating damage on a developed barrier island as sea levels rise - Patch, Stephanie M.; Collini, Renee C.; Delaney, Bailey R.; Bellais, Kaylyn; Heming, Mikaela; Caraway, Peyton (Frontiers in Ecology and Evolution, 2026)
Adaptation pathways are responsive planning tools intended to help decision-makers incorporate uncertainty of a future scenario while optimizing the use of their resources. In this project, an adaptation pathway was generated for a developed barrier island community, Dauphin Island, Alabama, USA. The project period was October 2019 to April 2022, with community engagement beginning in January 2020. Initial meetings were held with the community to identify vulnerable locations and co-develop adaptation strategies that were evaluated throughout the project. The effectiveness of adaptation strategies to reduce damage was estimated with a process-based numerical model, XBeach, which simulated inundation and morphological change due to Hurricane Nate (2017) and several sea-level rise scenarios. Depending on the Dauphin Island priority area, “damage” was defined as saltwater contamination in a freshwater lake, sand deposits on Dauphin Island’s main through route, or decreased sediment volume. When damage was sustained for a given strategy and sea-level rise scenario, a “tipping point” was reached and triggered the implementation of another strategy. Adaptation pathways were generated for two focus locations, with one location having two tipping points resulting in two pathways. This project revealed adaptation pathways are dependent on definitions of tipping points and location even within the same community. Community engagement revealed vulnerable locations that were previously unrealized and identified ‘reasonable’ or ‘unreasonable’ adaptation strategies based on community needs and desires. While the pathways produced for Dauphin Island are likely not transferrable to other locations, both findings are key to effective application of the adaptation pathways approach and generating a pathway accepted by the community.